Analysis of Internal and External Factors Affecting Stock Prices in the Energy Sector Listed on the Indonesia Stock Exchange During 2020–2024 - Destian Fazri Almadi; Antonius Herusetya (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The Indonesian energy sector plays a strategic role in supporting economic resilience, yet its stock performance has been highly volatile in recent years due to global commodity price fluctuations, macroeconomic instability, and major external shocks. This study aims to investigate the influence of internal financial indicators and external macroeconomic factors on the stock prices of energy-sector firms listed on the Indonesia Stock Exchange during the period 2020–2024. This study uses a quantitative method using multiple linear regression tests. The analysis includes 315 firm-year observations from 63 companies selected using purposive sampling. Profitability and leverage represent internal performance variables, while crude oil price, coal reference price, inflation, and exchange rate serve as macroeconomic predictors. The results reveal that profitability has a negative and significant effect on stock prices, while leverage shows no significant impact. Regarding macroeconomic factors, crude oil prices negatively influence stock prices, whereas coal prices, inflation, and the exchange rate exert positive and significant effects. The study concludes that stock price movements in the Indonesian energy sector are more strongly shaped by external macroeconomic conditions than by firm-specific financial ratios. These findings provide important insights for investors, managers, and policymakers in navigating the dynamics of a commodity-driven market.